The impact of bite force on the stability of dental implants - Nawres Bahaa Mohammed; Zina Ali Daily; Mohammed Rhael Ali; Noor Fathi Kazim; Hashim Mueen Hussein; Athraa Ali Mahmood (PLoS ONE, 2026)
Background Since dental implants (DI) are endo-osseous implants that are inserted into the bone and periodontium, which ultimately support the occlusal load, a patient’s bite force (BF) may overburden the supporting DI, leading to bone loss and DI failure. The purposes of this study were to explore the effect of the BF on DIs in different locations of jaws, of both genders during three visits, to investigate DI stability in different locations of jaws, of both genders during three visits, and to assess the association of BF and DI stability(ISQ) with the influence of variables (time, implant location, and gender). Methods The current cohort study involved 80 individuals of both genders who had lost some teeth and needed DIs for the anterior and posterior regions of the jaws. After the insertion of the DIs, their BF was examined by the Loadstar™ sensor, and the DI stability was monitored at three visits of these individuals. First visit during the day of insertion of the crown on the abutment of the implant (immediately loading), second visit at six months following insertion, and third visit after 18 months following insertion. Results The data on the anterior and posterior bite forces (BFs) for the male and female participants after the insertion of the DIs were analysed at three visits. On average, the males exhibited a significantly higher posterior BF compared to the females at the respective three visits. Similarly, the average posterior ISQ in the males was significantly increased than in the females at the respective three visits. Results of the two-way ANOVA of all groups for the implant BF and ISQ values were significantly influenced by the interaction of time, locations of the implants, and gender. The association between the BF and DI stability was significant in using the difference in the regression coefficient ( b ), which was impacted by time, implant location, and gender. Conclusions This study found the significantly complex interaction of factors (time, location, gender) influencing on change of BF and ISQ, by affecting the process of ossteointegration. The significantly higher BF in the posterior regions of males, and significantly greater stability of DIs, could have a potential role in the best DIs therapy. In addition, the association of the BF and DI stability is significantly established with the most important factors influencing the change in BF and DI stability. It varies in a dynamic manner as the interface between the bone and the implant matures, and the patient’s gender, time, and anatomical location all play a significant role in its context. The DIs that are loaded early is dependent on the BF. The BF may be crucial in determining the best DI stability.